Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10973-015-4746-2
|View full text |Cite
|
Sign up to set email alerts
|

Studies of thermal decomposition kinetics and temperature dependence of thermodynamic functions of the new precursor LiNiPO4·3H2O for the synthesis of olivine LiNiPO4

Abstract: The olivine LiNiPO 4 was synthesized via the calcination of the new precursor LiNiPO 4 Á3H 2 O at 600°C. The precursor was obtained from low-temperature (50°C) wet chemical reaction. The results from XRD, FTIR, AAS/ AES and TG/DTG/DTA techniques confirmed the formula of the title compounds. The SEM results indicated the morphologies of the hydrate precursor as thin plate particles and the calcined product as small bead particles. The BET surface area of the final calcined product at 600°C is much higher (5.807… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 59 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…The geometric models, widely used in the kinetic analysis of thermal decomposition reactions [20][21][22][23][24][25], are based upon the processes of nucleation and growth of product nuclei by interface advance. It was suggested that more reliable data can be obtained from the kinetic study of single crystals compared to powdery samples [1].…”
Section: Introductionmentioning
confidence: 99%
“…The geometric models, widely used in the kinetic analysis of thermal decomposition reactions [20][21][22][23][24][25], are based upon the processes of nucleation and growth of product nuclei by interface advance. It was suggested that more reliable data can be obtained from the kinetic study of single crystals compared to powdery samples [1].…”
Section: Introductionmentioning
confidence: 99%
“…The general equation 30,46,47 describing this theory is given as follows: kgoodbreak=χekBTphexp()ΔSRexp()goodbreak−EnormalaitalicRTnormalp where е = 27 183 is the Neper number; χ is the transition factor, which represents unity for monomolecular reactions; k B is the Boltzmann constant; h is the Planck constant; and T p is the peak temperature of the DTG curves at various heating rates. Taking into account that: A0.5emgoodbreak=0.5emitaliceχkBTph0.5emexp0.5em()ΔSR the thermodynamic functions Δ S ≠ , Δ H ≠ and Δ G ≠ , which well characterize the decomposition process, may be calculated 44,48,49 . Then, the changes in the entropy and enthalpy may be calculated according to the formulae: normalΔS0.5emgoodbreak=0.5emRlnAhitaliceχkBTp and normalΔH0.5emgoodbreak=0.5emEaRTp The change in the Gibbs free energy Δ G ≠ for the activated complex formation from the reagent can be calculated using the well‐known thermodynamic equation: normalΔGgoodbreak=normalΔHTPnormalΔS0.5em The values of Δ S ≠ , Δ H ≠ and Δ G ≠ were calculated at T = T p since this temperature characterizes the highest rate of the process, and therefore it is an important parameter.…”
Section: Methodsmentioning
confidence: 99%
“…In this process, the polymerization of the complex is stimulated by heating the transparent solution and a uniform resin in which metal ions are homogeneously dispersed at molecular level, which ultimately results in the formation of LN [12,13] or other lithium metal oxide [14] nanoparticles with outstanding chemical uniformity. Furthermore, it is pertinent to mention that the lack of Li loss is ensured by the use of low-temperature methods resulting in the control of chemical composition of the product [15,16]. Other advantages of the Pechini method include the possibility to work in aqueous solutions in which starting materials can be solved easily.…”
Section: Introductionmentioning
confidence: 99%